Acquisition of N-Glycosylation Sites in Immunoglobulin Heavy Chain Genes During Local Expansion in Parotid Salivary Glands of Primary Sjögren Patients - Visser, Annie; Doorenspleet, Marieke E.; de Vries, Niek; Spijkervet, Fred K. L.; Vissink, Arjan; Bende, Richard J.; Bootsma, Hendrika; Kroese, Frans G. M.; Bos, Nicolaas A. (Frontiers in Immunology, 2018)
Previous studies revealed high incidence of acquired N-glycosylation sites (ac-Nglycs) in RNA transcripts encoding immunoglobulin heavy variable region (IGHV) 3 genes from parotid glands of primary Sjögren’s (pSS) patients. In this study Next Generation Sequencing was used to study the extent of ac-Nglycs among clonally expanded cells from all IGVH families in the salivary glands of pSS patients. RNA was isolated from parotid gland biopsies of 5 pSS patients and 5 non-pSS sicca controls. IGHV sequences covering all functional IGHV genes were amplified, sequenced and analyzed. Each biopsy recovered 1800-4000 unique IGHV sequences. No difference in IGHV gene usage was observed between pSS and non-pSS sequences. Clonally related sequences with more than 0.3% of the total number of sequences per patient were referred to as dominant clone. Overall, 70 dominant clones were found in pSS biopsies, compared to 15 in non-pSS. No difference in percentage mutation in dominant clone-derived IGHV sequences was seen between pSS and non-pSS. In pSS no evidence for antigen driven selection in dominant clones was found. We observed a significantly higher amount of ac-Nglycs among pSS dominant clone-derived sequences compared to non-pSS. Ac-Nglycs were however not restricted to dominant clones or IGHV gene. Most ac-Nglycs were detected in the framework 3 region. No stereotypic rheumatoid factor rearrangements were found in dominant clones. Lineage tree analysis showed in 4 pSS patients, but not in non-pSS, the presence of the germline sequence from a dominant clone. Presence of germline sequence and mutated IGHV sequences in the same dominant clone provide evidence that this clone originated from a naïve B-cell recruited into the parotid gland to expand and differentiate locally into plasma cells. The increased presence of ac-Nglycs in IGHV sequences, due to somatic hypermutation, might provide B-cells an escape mechanism to survive during immune response. We speculate that glycosylation of the B-cell receptor makes the cell sensitive to environmental lectin signals to contribute to aberrant B-cell selection in pSS parotid glands.